Kościół w spluralizowanym świecie. Wpływ Karola Wojtyły na nauczanie Vaticanum Secundum o ekumenizmie i dialogu religijnym - SKRZYPCZAK, Robert (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2012)
Karol Wojtyła, who actively participated in all the sessions of the Second Vatican Council, was influential in the preparation of various Council documents. Nevertheless, it is unknown whether he had any direct involvement in determining the details of the religious and ecumenical dialogue, as was planned by the Council. His contribution in this respect consists rather in philosophical and theological elaboration on the concepts essential to the practice of the Church in this regard. This would involve especially three categories: person, freedom and dialogue. These are fundamental concepts to determine the directions of the practical missionary activity of the Church when it comes to striving for unity with the followers of Christ who are not Catholics, and in building bridges of understanding with the world of other religions, as well as with the world of denial of God. These concepts, together with the engagement in the dynamics of the work of the Second Vatican Council, significantly shaped the fields of interest of the future pope regarding the Council. Jesus Christ was the center of Wojtyła’s deliberations concerning the category of person during the Council. In Him, every person can achieve their ontological and moral completeness. Being a Christian means first and foremost man’s mysterious fulfillment in his personal and communal structure. The mission proposed by the Church is not so much about finding new followers of a specific religious concept as it is an opportunity given by God to every man, an opportunity to experience one’s humanity in its fullness. In this context, the Church neither is a stranger to the world nor identifies with it, but serves as a place where God meets man, who wishes to cross the borders of his own nature. To the Bishop of Cracow, «the world» meant an environment where specific people live. If the Council decided to address the world understood in such a way, then it had to get rid of the attitude of authoritative instruction, and especially of a monologue. Dialogue has to be the main tool for the activity of the Church directed «outside.» It enables focusing attention on the person and on the attainment of this person’s good without resorting to unnecessary theorizing which is not very effective. Each dialogue requires, however, an assurance of freedom. According to Karol Wojtyła, freedom is defined most accurately by the words of Christ: “Ye shall know the truth, and the truth shall make you free” (J 8:32). The main objective of the presence of the Church in the world is to reveal the truth about man’s relationship with God. This truth helps man to rebuild his inner value and respect for the world in which he is living. In this context, the dialogue with non-believers who experience ontological loneliness as a result of the lack of reference to the personal Creator can also prove helpful and constructive.